Efficacy of osimertinib in epidermal growth factor receptor-mutated non-small-cell lung cancer patients with pleural effusion - Hiroshi Nokihara; Hirokazu Ogino; Atsushi Mitsuhashi; Kensuke Kondo; Ei Ogawa; Ryohiko Ozaki; Yohei Yabuki; Hiroto Yoneda; Kenji Otsuka; Yasuhiko Nishioka (BMC Cancer, 2022)
Abstract Background Osimertinib is a standard first-line treatment for advanced non-small-cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations. Although malignant pleural effusion (PE) is a common clinical problem in NSCLC, information about the efficacy of osimertinib in patients with PE is limited, especially regarding its efficacy in EGFR T790M-negative patients with PE remains unclear. Methods We retrospectively reviewed the medical records of patients with NSCLC harboring EGFR mutations who were treated with osimertinib in our institution between May 2016 and December 2020. Results A total of 63 patients with EGFR mutated NSCLC were treated with osimertinib; 33 (12 with PE) had no EGFR T790M mutation, while 30 (12 with PE) had EGFR T790M mutation. In EGFR T790M-negative NSCLC, the progression-free survival (PFS) of the patients with PE was comparable to that of the patients without PE (median PFS 19.8 vs. 19.8 months, p = 0.693). In EGFR T790M- positive NSCLC, the PFS and overall survival (OS) of the patients with PE were significantly shorter than those of the patients without PE (median PFS 16.8 vs. 8.3 months, p = 0.003; median OS 44.9 vs. 14.2 months, p = 0.007). In the multivariate analysis, the presence of PE was independently associated with shorter PFS and OS in EGFR T790M-positive NSCLC patients, but not EGFR T790M-negative patients. Conclusions These data suggest the efficacy of osimertinib may differ between EGFR T790M-positive and -negative NSCLC patients with PE.